Pengembangan Aplikasi Ez-Health berbasis Android sebagai Upaya Mengukur Informasi Gizi dan Mendeteksi Jenis Makanan dengan Metode Object Detection - Farid Adi Wijaya S; Lutfi Fanani; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
In Indonesia, one of the most common health problems is obesity. Obesity is a condition where there is an excess amount of fat in the body. The attempt to do in overcoming obesity is applying a healthy lifestyle (a balanced exercise and diet). However, there is interference in implementing a healthy lifestyle especially in the healthy diet which is the lack of knowledge in measuring the daily nutritional needs. Therefore one of the ways to look for information is surfing internet which is less efficient and has a less attractive display. Therefore, the author made an innovation, EZ-Health application which can be implemented on the android platform with the Model View Presenter (MVP) development architecture. The main features of the EZ-Health application are to calculate daily calorie needs and to detect the type of food and its nutrition by utilizing Object Detection technology. Object Detection is one of Computer Vision technology that allows us to identify and discover objects in images or videos. For testing the EZ-Health application, the results obtained are: all functionality can run normally and comply the health aspect in the validation test. In testing the system accuracy with 10 foods set, the accuracy results obtained is 88%. Then in the Usability test using the SUS (System Usability Scale) method which involved 5 respondents, the EZ-Health application got a score of 76 with a Good, Acceptable, Passive interpretation scale. And lastly, in Compatibility testing carried out on 4 devices with Android api version 26 and above, all functionality in the application can work normally.